Effects of Polyvinyl Chloride Microplastics on the Reproductive System, Intestinal Structure, and Microflora in Male and Female Mice - Yang-Kai-Xin Yang; Shu-Jun Ge; Qi-Ling Su; Jin-Jun Chen; Jiang Wu; Kai Kang (Veterinary Sciences, 2024)
The pervasive use of plastics in numerous industrial sectors has resulted in the circulation of microplastics across diverse ecosystems and food chains, giving rise to mounting concerns regarding their potential adverse impacts on biological systems and the environment. The objective of this experiment was to investigate the distinct effects of microplastic-polyvinyl chloride (PVC) exposure on the reproductive system, intestinal tissue structure, and intestinal microbial flora of both male and female mice. A total of 24 4-week-old Kunming mice were randomly assigned to one of four groups: male control group (CM), female control group (CF), male PVC test group (PVCM), and female PVC test group (PVCF) (n = 6). The findings revealed that in terms of the reproductive system, the PVCM group exhibited an impaired testicular structure with an irregular arrangement and a significant reduction in spermatogonia, spermatocytes, and spermatozoa within the seminiferous tubules (p < 0.01). The PVCF group exhibited a notable decrease in ovarian follicles (p < 0.01), accompanied by a reduction in uterus volume, fallopian tube volume, and muscle layer thickness, all of which also decreased significantly (p < 0.01). In comparison to the control groups, exposure to PVC resulted in a reduction in the width and height of the intestinal villi, accompanied by an increase in crypt depth. This led to a significant alteration in the ratio of villus height to crypt depth (V/C) (p < 0.01). Moreover, a reduction in microbial species diversity was observed within both the PVCM and PVCF groups; additionally, it was accompanied by contrasting changes in relative abundance and functional gene profiles among the major intestinal flora constituents. In summary, the findings indicate that PVC induces damage to both male and female mice reproductive and digestive systems, further exhibiting notable sex-dependent effects on mouse intestinal microflora composition, which correlates significantly with its impact on reproductive organs.